2020
DOI: 10.12957/geouerj.2020.47278
|View full text |Cite
|
Sign up to set email alerts
|

A Dimensão Espacial Da Rede De Flores E Plantas Ornamentais Do Estado Do Rio De Janeiro: Uma Análise a Partir Do Município De Nova Friburgo, Entre Os Anos De 2002 E 2018

Abstract: Dados globais sobre o comércio mundial de flores e plantas ornamentais mostram o crescimento da produção e consumo desse segmento nas últimas décadas, inclusive no Brasil. Este artigo mostra como o comércio de flores e plantas ornamentais está organizado em forma de redes geográficas, na medida em que tanto a produção quanto o consumo articulam diferentes espaços. Na constituição da rede de flores e plantas ornamentais, torna-se imprescindível a identificação dos seus agentes ou elementos espaciais e das inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
4
1
3
Order By: Relevance
“…11 This study identified a greater strength of association of CM among mothers with lower educational levels, as well as those who had no or less than six prenatal consultations, corroborating other studies. 7,12 Although the number of prenatal consultations showed an association with CM in the bivariate analysis, this association cannot be confirmed in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 82%
“…11 This study identified a greater strength of association of CM among mothers with lower educational levels, as well as those who had no or less than six prenatal consultations, corroborating other studies. 7,12 Although the number of prenatal consultations showed an association with CM in the bivariate analysis, this association cannot be confirmed in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 82%
“…11 Este estudo identificou maior força de associação de MC entre mães com menor grau de escolaridade, bem como aquelas que fizeram nenhuma ou menos de seis consultas pré-natais, corroborando com outros estudos. 7,12 Embora o número de consultas pré-natal tenha mostrado associação com MC na análise bivariada, essa associação não pode ser confirmada na análise multivariada.…”
Section: Discussionunclassified
“…Isso leva a uma maior prevenção e detecção precoce de condições maternas que podem contribuir para o desenvolvimento de MC. 12,16 Embora o presente estudo tenha constatado maior prevalência de MC entre mães solteiras, outros estudos realizados no Brasil não observaram associação entre os tipos de malformações e situação conjugal. 16,17 Tabela 2 Prevalência de malformação congênita, segundo características sociodemográficas maternas, perfil obstétrico e perinatais, no período de 2015 -2019, em Rondônia.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In 2000, the search for ornamental plants led to an annual per capita consumption of R$ 20.00, moving around three billion reais per year [1]. In 2019, average consumption of BRL 31.50 per capita was recorded, representing an increase of 63.4%, with an estimated movement of around eight billion reais by the sector of the Brazilian landscaping market [2]. According to the Brazilian Institute of Floriculture (Ibraflor), the ornamental plant sector grew around 10% in 2020, and new purchase formats, such as delivery, promoting the market to 5% in 2021 [3].…”
Section: Introductionmentioning
confidence: 99%